Nordic best practices - Hillgrén, Anna (TemaNord, 2016)
The working group on Sustainable Consumption and Production, under the Nordic Council of Ministers requested consultants from Gaia to identify, write out and publish best practice cases of sustainable consumption and production on the UNEP SCP Clearinghouse. This report presents nineteen initiatives that cover two particular themes: 1) Sustainable Lifestyles and Education and 2) Sustainable Public Procurement. The cases have also been added into the UNEP's 10 Year Frame-work Program (10YFP) information platform, the SCP Clearinghouse which is a concrete result of Rio+20. The objective is to enhance international cooperation in order to accelerate a shift towards sustainable consumption and production in developed and developing countries. The SCP Clearinghouse is a web-based information sharing tool, which can be used by different actors as an inspiration for advancing SCP worldwide.